القانون المنظم للسجون أية حماية لحقوق الحدث الجانح - أسحاب، حميد (هشام الاعرج, 2021)
إن المؤسسات العقابية أو السجنية أو الإصلاحية باختلاف تسمياتها أصبحت تؤدي أدوارا أساسية في إصلاح سلوكيات المخالفين للضوابط القانونية، وتصبح هذه المؤسسات أكثر أهمية عندما تستقبل فئة الأحداث الجانحين أو الموجودين في نزاع مع القانون، حيث لابد لها من أن تؤدي تلك الأدوار الإصلاحية تجاه هذه الفئة الحساسة من المجتمع. هذا ما يجعلنا نتساءل هل فعلا هذه المؤسسات تؤدي هذه الأدوار انطلاقا من النصوص القانونية التي تؤطرها والبرامج التي تقدمها، أم أن الأمر خلاف ذلك؟ إن ذلك ما جعلنا نحاول البحث في هذه الإشكالية وذلك من خلال التطرق للمرتكزات التي أسس عليها هذا النص القانوني المنظم للمؤسسات السجنية، سواء على المستوى الدولي أو على المستوى الوطني، إضافة إلى محاولة الاطلاع على التطبيق العملي لهذا النص على المستوى الواقعي، وما يرافقه من تدابير وبرامج تأهيلية مخصصة للأحداث الجانحين يبتغي من ورائها الإصلاح وإعادة الإدماج في المجتمع. كل ذلك جعلنا نقف على نواقص وإشكاليات مختلفة، سواء على المستوى القانوني أو الواقع العملي تتطلب التدخل الآني والمستقبلي من أجل تجاوزها، وهو ما تمت ترجمته إلى مقترحات من داخل ثنايا هذا المقال العلمي المتخصص. The punitive, penitentiary or correctional establishments, with their different names, they have essential roles in the reform of the behavior of the violators of the legal rules, these establishments become more important when they receive the category of young delinquents or in conflict with the law, because they have to play these correctional roles towards this sensitive group. This raises the question of whether these institutions really fulfill these roles according to the legal texts that frame them and the programs they provide, or is it otherwise? This is what made us attempt to research this problem by addressing the pillars on which this legal text regulating penitentiary institutions was founded, whether at the international or national level, in addition to trying to see the practical application of this text on the realistic level and the measures and support programs dedicated to the rehabilitation of young delinquents in order to reform them and reintegrate them into society. All of this has led us to oppose various shortcomings and issues, both legal and practical, that require immediate and future intervention in order to overcome them, which has been translated into proposals within this specialized scientific article.
Keywords: القوانين والتشريعات -- المؤسسات العقابية -- السجون -- الأحداث الجانحة